A longitudinal study on the phenomenon of street children and their likelihoods to join juvenile gangs upon transient from the adolescence - Wijewardhana, B.V.N. (International Journal of Humanities and Social Science Research, 2017)
This research aimed at to investigate the lived experiences of the street children in Colombo, Sri Lanka, although street children can be found in several other towns as well and the perspectives may vary regionally. The main purpose of the study was to portray the diversified responses of the street children's experiences;tbrough a longitudinal study. Also envisioned to come up with predictable views on their life style characterized in accordance with their socio-economic, religious and cultural occurrences. In most cases the responsible agencies, such as government institutions and non-government agencies are to define distinctiveness of the street children. But this study wanted to get directly examine the current life styles of street children, their future and the tendencies to join criminal gangs. This research was initiated in 2005 in Colombo and concluded in 2015 in three phases. The two initial phases which were concluded in 2010 were directly focused on street children while pbase three implemented from 2011 - 2015 was straightforwardly concentrated on Youth gangs enclosing 631 ganged youth in mixed ages and 491 of those in age from 18 to 32 years. The theoretical methodology of the study is guided by an affirmative research paradigm. In Phase 1, 20 semi structural interviews (SSIs) and the key informants were the parents or guardians of the street children. All interviewee samples were identified through snow-ball technique and a random samples. The total children selected for research were 256 and 190 male children representing 76% of the total. Research carried out from 2011 to 2015 on urban ganged youth from age between 18 - 32 to determine the relationship that existed between gang members and the youth who passed childhood as street children. Studying the jeopardy of street children joining criminal gangs. when they grow up too, became essential in the study. Keywords: street children, longitudinal study, juvenile, gangs, adolescence
Keywords: street children, longitudinal study, juvenile, gangs, adolescence